2021
DOI: 10.1101/2021.01.01.20248966
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survival analysis of all critically ill patients with COVID-19 admitted to the main hospital in Mogadishu, Somalia, 30 March–12 June 2020: what interventions are proving effective?

Abstract: OBJECTIVES To determine risk factors for death in patients with COVID-19 admitted to the main public sector hospital in Somalia and identify interventions contributing to improved clinical outcome in a low resource and fragile setting. SETTING Main public sector tertiary hospital in Mogadishu, Somalia. PARTICIPANTS All 131 laboratory confirmed COVID19 patients admitted to the main public tertiary hospital in Somalia between 30 March and 12 June 2020. MAIN OUTCOME MEASURES We extracted demographic and clinical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
0
2
1
Order By: Relevance
“…43,48,53,54 Another survival analysis performed on 131 patients hospitalized in the main hospital in Mogadishu even documented a mortality rate of 40%. 55 The proportion of adverse outcomes in our study population is low even in comparison with studies from high income countries. One large-scale multicenter observational study including almost half a million hospitalized COVID-19 patients from 49 different countries for example, showed a mortality of 20%.…”
Section: Multivariable Survival Analysiscontrasting
confidence: 57%
“…43,48,53,54 Another survival analysis performed on 131 patients hospitalized in the main hospital in Mogadishu even documented a mortality rate of 40%. 55 The proportion of adverse outcomes in our study population is low even in comparison with studies from high income countries. One large-scale multicenter observational study including almost half a million hospitalized COVID-19 patients from 49 different countries for example, showed a mortality of 20%.…”
Section: Multivariable Survival Analysiscontrasting
confidence: 57%
“…3 According to a research conducted by De Martino Hospital, Somalia’s largest and only public sector hospital, 131 patients were admitted between March 30 and June 12, 2020, with 79/131 (60%) being discharged and 52/131 (40%) died during hospitalization. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Kundu and Mandal (2020) carried out a survival analysis to establish the variability in survivorship among age groups and sex at different levels that is national, state and district level in india. Ali et al (2020) implemented survival analysis to determine risk factors for death in patients with COVID-19 admitted to the main public sector hospital in Somalia and identify interventions contributing to improved clinical outcome in a low-resource and fragile setting. Implementing multivariate Cox-PH model (Wang et al, 2020) found that preparation control measures of COVID-19 should involve the allocation of sufficient medical resources, especially in areas with older vulnerable populations and in areas that lack basic medical resources.…”
mentioning
confidence: 99%